Fast Charging Lithium Batteries: Recent Progress and Future Prospects - Zhu, Gao‐Long; Zhao, Chen‐Zi; Huang, Jia‐Qi; He, Chuanxin; Zhang, Jian; Chen, Shaohai; Xu, Lei; Yuan, Hong; Zhang, Qiang (Small (Weinheim an der Bergstrasse, Germany), 2019)
Fast charging enables electronic devices to be charged in a very short time, which is essential for next‐generation energy storage systems. However, the increase of safety risks and low coulombic efficiency resulting from fast charging severely hamper the practical applications of this technology. This Review summarizes the challenges and recent progress of lithium batteries for fast charging. First, it describes the definition of fast charging and proposes a critical value of ionic and electrical conductivity of electrodes for fast charging in a working battery. Then based on this definition, the requirements and optimization strategies of the electrode, electrolyte, and electrode/electrolyte interface for fast charging are proposed. Finally, a general conclusion and perspectives on the better understanding of lithium batteries with fast charging capability are presented. The fast charging of rechargeable batteries is reviewed and the critical values of ionic and electrical conductivity of electrodes that are employed in fast charging are also proposed. The requirements of electrode, solid electrolytes, and their interfaces are also presented to meet the practical application in fast charging batteries.